Application of Placental Blood Serum to Correct Disordered Morphofunctional State of Adrenal Glands at Experimental Atherosclerosis - Falko, Oksana V.; Prokopyuk, Olga S.; Volina, Viktoriya V.; Lipina, Olga V. (Problems of Cryobiology and Cryomedicine, 2013)
In the model of experimental atherosclerosis in rabbits there was studied the effect of human placental blood serum on lipid spectrum and morphofunctional state of adrenal glands. It has been shown that placental blood serum contributes to an increase in antiatherogenic fraction of lipoproteids in rabbits blood and recovery of morphological structure of adrenal glands, however does not result in the restoration of functional activity of glands to the mentioned observation terms.Probl Cryobiol Cryomed 2013; 23(1):75–83.